(untitled) (Acta Scientiarum. Technology, 2012)
The use of water in a hydrographic basin within the Amazon deforestation area is evaluated as a case study for the municipality of Rondon do Pará, State of Pará, Brazil. Current investigation takes into account the hydrographic basin as a system, following the Pressure/State/Response concept model, and aims at an analysis of the system´s sustainability. Results show that the use of water within the context of the system under analysis tends towards non-sustainability. Economic growth, especially triggered by the expansion of extensive cattle-raising and industrial activities, has worsened the situation. These conditions do not represent local reality since the above-mentioned activities have produced only scanty employment. Further, the municipality is striving with problems concerning the supply of drinking water, deficiency in sewage treatment and especially the deterioration of surface water resources. Â